2022
DOI: 10.3390/foods11020209
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Storage Time and Environmental Storage Conditions on Flour Quality, Dough Rheology, and Biscuit Characteristics: The Case Study of a Traditional Italian Biscuit (Biscotto di Prato)

Abstract: Many types of baked goods are firmly rooted in the food habits of many people in different countries. Although there have been great strides in improving milling, kneading, and baking, given the lack of essential studies, further steps forward need to be taken to understand the effects of storage time and environmental storage conditions, thus motivating this work. The aim of this study is to assess the effects of storage time, using one-way ANOVA, and environmental storage conditions (environmental temperatur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 29 publications
0
9
0
Order By: Relevance
“…As for strength, it increased in the two treatments A and C, which were 19 for each, while it decreased for the standard treatment to reach 16, which was the lowest level among the treatments. The difference in the additions enhances the sensory characteristics studied and in some of the treatments reduces these characteristics due to the quantity and quality of the addition to the biscuit mixture [15,16]. One of the most important features of biscuits is its soft texture and rapid crumbling, but studies have shown that additives to the biscuit mixture change the characteristics of the biscuit, especially its hardness, and in most cases increase its storage period at room temperature, as the results of Table 5 showed differences in the storage period for the different types produced in the research, so it was higher The value of treatment A for the storage periods from the first day until the 28th day, as it recorded (4.32, 5.33, 6.03, 6.66, 7) days, respectively, while the least solid was in treatment C for the period (0,7,14), which recorded (3.35, 3.37, 3.55) respectively -but in the storage period (21, 28) days, it was for treatment D, which amounted to (3.70, 3.78), respectively.…”
Section: Resultsmentioning
confidence: 99%
“…As for strength, it increased in the two treatments A and C, which were 19 for each, while it decreased for the standard treatment to reach 16, which was the lowest level among the treatments. The difference in the additions enhances the sensory characteristics studied and in some of the treatments reduces these characteristics due to the quantity and quality of the addition to the biscuit mixture [15,16]. One of the most important features of biscuits is its soft texture and rapid crumbling, but studies have shown that additives to the biscuit mixture change the characteristics of the biscuit, especially its hardness, and in most cases increase its storage period at room temperature, as the results of Table 5 showed differences in the storage period for the different types produced in the research, so it was higher The value of treatment A for the storage periods from the first day until the 28th day, as it recorded (4.32, 5.33, 6.03, 6.66, 7) days, respectively, while the least solid was in treatment C for the period (0,7,14), which recorded (3.35, 3.37, 3.55) respectively -but in the storage period (21, 28) days, it was for treatment D, which amounted to (3.70, 3.78), respectively.…”
Section: Resultsmentioning
confidence: 99%
“…The antioxidant capacity of BG cookies was determined by employing three antioxidant assays. 2,2-Diphenyl-1-picrylhydrazyl (DPPH) radical scavenging assay was executed using the protocol described by Cappelli et al 14 A freshly prepared 2 mL ethanol solution of 0.1 mM DPPH free radical (4 mg/100 mL) was mixed with 50 μL of aqueous solution of the respective cookie extracts and 500 μL of Tris HCl buffer (pH 7.4). The absorbance was measured at 517 nm.…”
Section: ■ Materials and Methodsmentioning
confidence: 99%
“…The textural analysis of cookies was determined using a Textural Analyzer (Imada, Toyohashi, Japan) by using a flat cylindrical probe (2 cm diameter). 14 Color Analysis of Cookies. The color of the cookies was analyzed using a digital colorimeter (Konika Minolta, CR-20, Tokyo, Japan) 15 CIELab color scale was used to get L*, a*, and b*values.…”
Section: ■ Materials and Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, the flavor of bread could change according to several factors such as raw material ratios, recipe, fermentation processes (direct or indirect methods), and fermented strains (Anna et al., 2018; Cappelli et al., 2022; Venturi et al., 2022). In terms of raw material ratios, flour is mixed with multigrain crops rich in a variety of trace elements (such as buckwheat, oats, kidney beans, potatoes, etc.)…”
Section: The Main Flavor Substances Produced By Bread Bakingmentioning
confidence: 99%